(untitled) (Sains Humanika, 2017)
Mathemagics or ‘Magic Maths’ consists of a series of non-conventional maths formulas that turn Mathematics into a fun subject and create innovative minds. The magical system could help steer the country towards a knowledge economy. The magic formulas, based on Ancient Indian Scriptures, were in use by the United States National Aeronautics and Space Administration (NASA), Intel Corporation, Microsoft, IBM and India, for its competitive exams preparations. The high speed mental mathematics could speed up math calculation by up to 1500 % and turn students into human bio-calculators. Mathemagics presents varieties of methods which can be used according to one’s needs in solving even the most difficult math problems. This is unlike the conventional system consisting of rigid, sometimes monotonous, procedures that are uniformly applied to all problems of a given type. The conventional method of calculation was not user – friendly with hardly any room for choice and experimentation. A seemingly difficult calculation like 998 x 997 can be solved in less than five seconds and even mentally. There is also a unique method to check the accuracy of answers to addition, subtraction, multiplication and division, in keeping with the basic needs of students for faster calculations with 100 % accuracy. Innovation of the formula would make students become more confident and gain self – esteem while cultivating an interest for numbers and help eliminate math – phobia in them. The system also opens a new horizon for mathematics lovers as it presents a wider platform for experimentation in the subject. Besides, it promotes development of the right brain which governs the ability to solve complex calculations that require the use of visualization, photographic memory, speed reading and sub-conscious learning together with the left – brain that is employed by students for 90 % of subjects taught at school.